2009
DOI: 10.1037/a0012385
|View full text |Cite
|
Sign up to set email alerts
|

Spouses' use of pressure and persuasion to promote osteoarthritis patients' medical adherence after orthopedic surgery.

Abstract: Although there are often immediate behavioral benefits in response to partners' use of both pressure and persuasion, the long-term health effects of these strategies seem to be accounted for by their opposing links to positive emotions. Findings further refine theory on health-related social control in marriage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
109
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 47 publications
11
109
1
Order By: Relevance
“…Persuasive social support strategies involving efforts to prompt or persuade another person to improve his or her health behaviors have been found to elicit positive health behavior change (Stephens et al 2009), whereas control strategies that involve the use of pressure, such as criticizing or expressing doubts about the person's health behavior, have been found to undermine behavior change (Martire et al 2013). Participants were asked to indicate the frequency with which their partner used social persuasion (3 items) and social pressure (4 items) to influence their health behaviors.…”
Section: Exploratory Secondary Measuresmentioning
confidence: 99%
“…Persuasive social support strategies involving efforts to prompt or persuade another person to improve his or her health behaviors have been found to elicit positive health behavior change (Stephens et al 2009), whereas control strategies that involve the use of pressure, such as criticizing or expressing doubts about the person's health behavior, have been found to undermine behavior change (Martire et al 2013). Participants were asked to indicate the frequency with which their partner used social persuasion (3 items) and social pressure (4 items) to influence their health behaviors.…”
Section: Exploratory Secondary Measuresmentioning
confidence: 99%
“…Miller et al (1992) found that peer-pressure predicts patients' intention to adhere to prescribed treatments, which in turn influences adherence to lifestyle changes. The use of pressure and persuasion strategies by spouses has also been linked to greater adherence (Stephens, Fekete, Franks, Rook, Druley & Greene, 2009). However, another group of researchers reported that when friends and family members have strong opinions about asthma patients' medication use, patients were less likely to take their medications (Foster et al, 2011).…”
Section: Interpersonal Factorsmentioning
confidence: 99%
“…This can have a positive impact on improving the elderlys' quality of life; however, the potential risk is that the shared information may contain inaccurate or even harmful details, especially concerning chronic and life-threatening conditions (22). On the other hand, the elderly in social networks have the ability to persuade each other to treat and adhere to medical treatments, which shortens the recovery period (24). This can be used in social networks and aging can be accompanied by more health through elaborating such networks and uploading the correct, reliable, and authentic information.…”
Section: Discussionmentioning
confidence: 99%